2020
DOI: 10.1136/tobaccocontrol-2019-055345
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smokers’ concurrent use of smokeless tobacco: dual use patterns and nicotine exposure

Abstract: BackgroundThe concurrent use of cigarettes with other tobacco products, such as smokeless tobacco (SLT), is increasingly common. Extant work with cigarette smokers who also use SLT is based heavily on retrospective reports and between-group comparisons. The purpose of this study was to assess prospectively the patterns of dual users’ product use and nicotine exposure on days when cigarettes were smoked exclusively (single use) versus concurrently with SLT (dual use).DesignForty-six dual cigarette-SLT users rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…While we have no direct evidence, the product use behavior may be different among exclusive smokers or exclusive MST users vs. dual users of cigarettes and MST products. There is some evidence of differential product use behavior; for example, Felicione et al ( 2020 ) observed significantly lower cotinine levels among dual users on days when they only smoked cigarettes as opposed to when they dual used both cigarettes and MST. Additional factors likely contributing to the lower-than-expected nicotine delivery could be due to differences in own brand products or inherent inter-subject variability, including variations in use behavior, such as the size of the MST quid used in the ad libitum vs. controlled use periods.…”
Section: Discussionmentioning
confidence: 99%
“…While we have no direct evidence, the product use behavior may be different among exclusive smokers or exclusive MST users vs. dual users of cigarettes and MST products. There is some evidence of differential product use behavior; for example, Felicione et al ( 2020 ) observed significantly lower cotinine levels among dual users on days when they only smoked cigarettes as opposed to when they dual used both cigarettes and MST. Additional factors likely contributing to the lower-than-expected nicotine delivery could be due to differences in own brand products or inherent inter-subject variability, including variations in use behavior, such as the size of the MST quid used in the ad libitum vs. controlled use periods.…”
Section: Discussionmentioning
confidence: 99%
“…Although cotinine concentrations in urine are correlated with those in saliva, concentrations are consistently higher in the former fluid (Shaik et al, 2019). Another difference is that the cigarette smokers included herein used SLT regularly; dual cigarette-SLT users’ salivary cotinine concentrations are higher on days when both products are used relative to when only cigarettes are smoked (Felicione et al, 2020). Participants’ SLT use was controlled for in regression analyses, though additional work should examine whether either measure is consistent with exposure to cotinine in a sample of cigarette smokers who do not use other tobacco products.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, spent filter collection is inexpensive and likely requires less effort from participants than using an electronic diary (Saddleson et al, 2017). On the other hand, electronic diaries can collect a wealth of information about the context of cigarette smoking, such as location of use, concurrent engagement in other behaviors, and mood (Felicione et al, 2020; Ferguson et al, 2015). For researchers who do not need to evaluate contextual-level factors, returned filters may offer a cost-effective and convenient tool for reliable measurement of smoking behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review found few primary studies investigating the possible association between snus and changes in smoking behaviour ( SBU 2020 ). However, it is noteworthy that (1) snus may serve as a gateway for smoking, at least among Finnish adolescents ( Araneda et al, 2020 ; SBU, 2020 ), (2) many school children end up as dual users ( European Commission, 2012 ; FCTC, 2012 ; Felicione et al, 2020 ; Lund & Scheffels, 2016 ; Ollila & Ruokolainen, 2016 ), (3) nicotine is also harmful in itself, especially for the developing body, including the brain ( Drug and Therapeutics Bulletin, 2014 ; USDHHS 2014 ; Viarisio, 2015 ), and (4) that snus carries considerable health risks ( European Commission, 2012 ; Folkehelseinstituttet, 2019 ; IARC, 2018 ; SCENIHR et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%